A New Approach - Global Financial Governance (International Journal of Food and Nutritional Sciences, 2022)
The post-pandemic economic scenario is akin to the Mona Lisa, revealing differentaspects with each observation. Amidst the banking industry chaos, many analysts now foresee apotential "hard-landing" recession for the world economy. The once-popular notion of a "nolanding" scenario, untouched by rising interest rates, has faded, replaced by the current belief inan imminent economic downturn.